Tracks: Industrial Economics, Social Welfare, Infrastructure, Tourism, Business Strategy, Innovation, and Entrepreneurship - Panitia - (UPT Penerbitan Universitas Jember)
Tracks: Industrial Economics, Social Welfare, Infrastructure, Tourism, Business Strategy, Innovation, and Entrepreneurship